Dietary Micronutrient Intakes Are Associated with Markers of Inflammation but Not with Markers of Subclinical Atherosclerosis(2) - de Oliveira Otto, Marcia C. C. (American Society for Nutrition, 2011)
Few studies have examined associations of dietary micronutrients with markers of inflammation and subclinical atherosclerosis. The present study investigated associations of heme iron, nonheme iron, zinc (Zn), magnesium (Mg), β-carotene, vitamin C, and vitamin E with C-reactive protein (CRP), IL-6, total homocysteine (tHcy), fibrinogen, coronary artery calcium, and common and internal carotid artery intima media thickness. Micronutrient intakes and markers of inflammation and subclinical atherosclerosis were studied in 5181 participants from the Multi-Ethnic Study of Atherosclerosis who were aged 45–84 y and free of diabetes and cardiovascular disease. Models were adjusted for energy intake, demographics, lifestyle characteristics, and BMI. Dietary nonheme iron and Mg intakes were inversely associated with tHcy concentrations (mean tHcy: 9.11, 8.86, 8.74, 8.71, and 8.50 μmol/L, and 9.20, 9.00, 8.65, 8.76, and 8.33 μmol/L across increasing quintiles of nonheme iron and Mg, respectively; P-trend < 0.001 for both). However, dietary Zn and heme iron were positively associated with CRP [mean: 1.73, 1.75, 1.78, 1.88, and 1.96 mg/L across increasing quintiles of Zn and 1.72, 1.76, 1.83, 1.86, and 1.94 mg/L across increasing quintiles of heme iron (P-trend = 0.002 and 0.01, respectively). Other tested micronutrient-marker associations were not significant. In conclusion, of the 49 tested associations, only 7 were significant. Although this study does not provide strong support for associations between the micronutrients and markers of inflammation and subclinical atherosclerosis, the results are consistent with dietary guidelines that advocate for a balanced diet that includes a variety of plant foods containing Mg, Zn, and nonheme iron.